BRIDGING THE GAP FROM STUDENT TEACHER TO CLASSROOM TEACHER - Whitford, Ellen (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This study focuses on providing support for beginning teachers to increase retention in the career. Despite strong requirements for teacher preparation, the attrition rate for new teachers continues to show that many novice teachers leave the profession within the first four years or less. This qualitative case study of teachers who completed a Professional Development School Model for teacher preparation has shown success in teacher readiness for the classroom and in retention in the career. Interview data showed positive outcomes including confidence in the content and pedagogical skills and a strong expectation for continuation in the teaching career. However, identified gaps in the transition phase during the first year suggest that additional support is needed to assure a successful first year and ongoing retention. Key variables are identified, including adaptation to different school culture, feelings of isolation, lack of support, and uncertainty about job expectations. These negatively impact success in the first year. Interventions and strategies to prevent these gaps in a successful transition are described. The Professional Development School Model can include preparation to help beginning teachers anticipate initial challenges. Optimum support includes focused actions by the school district, the school, and particularly, the school principal. Support strategies include mentoring, communication of clear expectations, strong instructional leadership, availability of resources, opportunities for professional development, and a focus on wellness. Future study should address the impact of the implementation of these strategies to bridge the gap in success in the first year and retention in the career.